Images of Delinquent Girls: Gender Stereotyping in Canadian News Representations, 1900–1979 - Faucher, Chantal (Atlantis, 2013)
This article presents a thematic analysis of gender in Canadian print media portrayals of female delinquency, 1900-1979. Girls’ wrongdoing has historically been treated as unnatural and requiring further explanation. The main thrust of media representations of delinquent girls centres on these girls’ (perceived) promiscuity and the threat it poses to the hegemonic order.